Divergent transcriptional responses to low temperature among populations of alpine and lowland species of New Zealand stick insects (Micrarchus). Issue 11 (16th May 2014) - Dunning, Luke T.; Dennis, Alice B.; Sinclair, Brent J.; Newcomb, Richard D.; Buckley, Thomas R.
Abstract In widespread and genetically structured populations, temperature variation may lead to among‐population differentiation of thermal biology. The New Zealand stick insect genus Micrarchus contains four species that inhabit different thermal environments, two of which are geographically widespread. RNA‐Seq and quantitative PCR were used to investigate the transcriptional responses to cold shock among lowland and alpine species to identify cold‐responsive transcripts that differ between the species and to determine whether there is intraspecific geographical variation in gene expression. We also used mitochondrial DNA, nuclear 28S ribosomal DNA and transcriptome‐wide SNPs to determine phylogeographic structure and the potential for differences in genetic backgrounds to contribute to variation in gene expression. RNA‐Seq identified 2160 unigenes that were differentially expressed as a result of low‐temperature exposure across three populations from two species (M. hystriculeus and M. nov. sp. 2), with a majority (68% ± 20%) being population specific. This extensive geographical variation is consistent across years and is likely a result of background genetic differences among populations caused by genetic drift and possibly local adaptation. Responses to cold shock shared among alpine M. nov. sp. 2 populations included the enrichment of cuticular structure‐associated transcripts, suggesting that cuticle modification may have accompanied colonization of low‐temperature alpine environments and the development of a more cold‐hardy phenotype.